IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK BERBANTUAN SOFTWARE GEOGEBRA TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS MATERITRIGONOMETRI KELAS X - Fitriana Fitriana; Venissa Dian Mawarsari; Abdul Aziz (Universitas Muhammadiyah Semarang, 2017)
This study aims to determine the implementation of cooperative learning model type Pair Check Software Geogebra assisted on the ability to understand the mathematical concepts of class X trigonometric material is achieving effective learning. This research is an experimental research. The population of this study are all classes of X MIPA. The independent variables in this research are process skill and independence, while the dependent variable is ability of comprehensionof mathematical concept. The results of this study indicate that: (1) learners using Geogebra software assisted Pair Check model achieved completeness of 85.294% more than 80% with the completeness criterion 75, (2) the effect test showed the influence of independence and process skill towards understanding mathematical concept in application of learning model type of Pair Check Software Geogebra assisted by 81,9%. (3) Different test results show that there is a difference in theaverage ability of understanding of mathematical concepts between using a type of learning model of Pair Check with Geogebra Software assisted by 80.00 with an expository learning model of 75.470. Based on those three things, it shows that the implementation of Pair Check model is Geogebra Software Assisted on the ability to comprehend mathematical concepts of effective class trigonometric materials. Keywords: Pair Check, Geogebra Software, Understanding concept